2003
DOI: 10.1038/sj.gt.3302074
|View full text |Cite
|
Sign up to set email alerts
|

Illegitimate DNA integration in mammalian cells

Abstract: Foreign DNA integration is one of the most widely exploited cellular processes in molecular biology. Its technical use permits us to alter a cellular genome by incorporating a fragment of foreign DNA into the chromosomal DNA. This process employs the cell's own endogenous DNA modification and repair machinery. Two main classes of integration mechanisms exist: those that draw on sequence similarity between the foreign and genomic sequences to carry out homology-directed modifications, and the nonhomologous or '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
132
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 108 publications
2
132
0
2
Order By: Relevance
“…Homology-dependent integration depends on homologous recombination (HR) repair proteins and the extent of homology between foreign and endogenous DNA (10)(11)(12). Illegitimate integration inserts exogenous DNA into nonhomologous genomic sequences and is far more efficient, probably in part because of the much larger number of potential illegitimate integration sites.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Homology-dependent integration depends on homologous recombination (HR) repair proteins and the extent of homology between foreign and endogenous DNA (10)(11)(12). Illegitimate integration inserts exogenous DNA into nonhomologous genomic sequences and is far more efficient, probably in part because of the much larger number of potential illegitimate integration sites.…”
mentioning
confidence: 99%
“…Exogenous DNA is usually integrated into the genome by two mechanisms: homology-dependent integration and illegitimate integration (10). Homology-dependent integration depends on homologous recombination (HR) repair proteins and the extent of homology between foreign and endogenous DNA (10)(11)(12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…58 Although adenovirus-derived vectors and Sendai virus were proclaimed as safe nonintegrating methods for production of iPSCs, the statement should be used with extreme caution. Harui et al 59 have reported that in established cell lines, adenoviral vectors do integrate into the genome.…”
Section: Mirna and Regenerative Medicinementioning
confidence: 99%
“…Genomic integration following viral transduction increases the risk of modifying recipient chromosomal locus making the recipient genomic loci unstable. 28 Although the integration frequency of adenovirus into chromosomal DNA in vitro was estimated to be in the order of 10 À3 to 10 À5 events per cell, 29 caution should be exercised while assessing in vivo risks based on such in vitro data. Do RNA viruses integrate into the host genome?…”
Section: Challenges In Gene Delivery and Mirna Solutionsmentioning
confidence: 99%